2017
DOI: 10.1111/jth.13787
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of a select one‐stage activated partial thromboplastin time‐based clotting assay and two chromogenic assays for the post‐administration monitoring of nonacog beta pegol

Abstract: Background Nonacog beta pegol (N9-GP) is an extended half-life, glycoPEGylated recombinant human factor IX that is under development for the prophylaxis and treatment of bleeding episodes in hemophilia B patients. Considerable reagent-dependent variability has been observed when one-stage clotting assays are used to measure the recovery of recombinant FIX products, including N9-GP. Objective To qualify select one-stage clotting and chromogenic FIX activity assays for measuring N9-GP recovery. Methods The accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 16 publications
4
53
1
Order By: Relevance
“…These results demonstrate that chromogenic coagulation assays produce accurate and consistent measurements that are independent of the PEGylation status of the FIX molecule and that the PEG moiety attached to N9‐GP does not interfere with the reagents used in the available chromogenic assays (Table ). FIX chromogenic assays can also reliably quantify the total FIX activity in samples containing both N9‐GP and unmodified FIX, providing additional advantage…”
Section: Recommendations For N9‐gp Postinfusion Monitoringmentioning
confidence: 74%
“…These results demonstrate that chromogenic coagulation assays produce accurate and consistent measurements that are independent of the PEGylation status of the FIX molecule and that the PEG moiety attached to N9‐GP does not interfere with the reagents used in the available chromogenic assays (Table ). FIX chromogenic assays can also reliably quantify the total FIX activity in samples containing both N9‐GP and unmodified FIX, providing additional advantage…”
Section: Recommendations For N9‐gp Postinfusion Monitoringmentioning
confidence: 74%
“…Currently, there is no international consensus of the degree of variation between reagents or assay methods measuring the same parameter which could be expected to alter the clinical management of patients. About 20%‐30% difference has been considered acceptable in several studies . At FIX:C below 10 IU/dL, the calculation of percentages can magnify small differences in activity which may not be clinically significant.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The over‐recovery of N9‐GP by most silica‐based APTT reagents has recently been explained by Rosén et al, who found that N9‐GP was prematurely converted to activated FIX (FIXa) during the contact activation phase of the clotting assay. Another recent three‐site study measuring recovery of N9‐GP at four spike levels using Rossix and Hyphen CSA concluded these assays were able to measure N9‐GP using a ± 30% of target as acceptable . The suitability of CSA for measuring the third current EHL product, rFIX‐Fp, remains unclear .…”
Section: Discussionmentioning
confidence: 99%